2014
DOI: 10.1007/s10461-014-0844-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sexual Health in the Virtual Environment: A Multinational Online Survey of Spanish- and Portuguese-Speaking Men who use an Internet Sexual Networking Site

Abstract: There is limited data on the sexual health of users of sexual networking websites for men who have sex with men (MSM) in Latin America. Members of a MSM-targeted social/sexual networking website in Latin America, Spain, and Portugal participated in an online sexual health survey. Among 36,063 respondents, nearly 90 % reported having anal or vaginal intercourse in the past 3 months. Among sexually active men, 53.2 % used condoms inconsistently. In the past year, 54 % of respondents reported undergoing sexually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The degree of attrition and non-response was similar to other online surveys. 43,44 Demographic characteristics were roughly balanced between individuals who completed the PrEP questions and those who did not, however there may have been differences in participants who did and did not complete PrEP questions that could affect estimates. We attempted to account for bias potentially introduced by missing data for items that were towards the end of the survey, including depression and alcohol dependency, and related to sexual behaviors, for which a substantial proportion of participants reported that they preferred not to answer the questions.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of attrition and non-response was similar to other online surveys. 43,44 Demographic characteristics were roughly balanced between individuals who completed the PrEP questions and those who did not, however there may have been differences in participants who did and did not complete PrEP questions that could affect estimates. We attempted to account for bias potentially introduced by missing data for items that were towards the end of the survey, including depression and alcohol dependency, and related to sexual behaviors, for which a substantial proportion of participants reported that they preferred not to answer the questions.…”
Section: Discussionmentioning
confidence: 99%
“…The survey aimed to collect data on sexual health and psychosocial risk among MSM using the internet for sexual networking. Details of this study have been published elsewhere (Biello et al, 2014 ). In brief, an email with a link to the survey was sent to nearly 580,000 active members (i.e., had logged on in past 90 days) in Latin America.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents completed an anonymous survey to characterize sexual health, including sexual practices, substance use, and relevant psychological concerns. The measures used for this analysis are described below and have been described in detail elsewhere (Biello et al, 2014 ; Magidson et al, 2015 ; Mimiaga et al, 2015a ).…”
Section: Methodsmentioning
confidence: 99%
“…Men who use the Internet to meet other men may present a different behavioral profile than men who meet men in physical venues. For instance, MSM who do not identify as such would be excluded from venue-sampling [ 38 ]. Therefore, a better understanding of the profile of MSM who use apps for sexual encounters is needed in order to design tailored, combined prevention interventions.…”
Section: Introductionmentioning
confidence: 99%